Drying-enhanced polyvinyl alcohol-polyacrylic acid double-network hydrogel and its application in flexible strain sensors. (31st December 2022) - Liu, Jiawei; Liu, Xing; Chen, Jiao; Wang, Hanhan; Han, Xia; Liu, Honglai
Highlights: A "freezing-drying-swelling" cycle enhanced properties of PVA-PAA hydrogels. FDS hydrogel reached a high tensile stress of 1.1 MPa at strain of 648%. The combination of conductive ions and PAA improved the conductivity of hydrogel. FDS hydrogel possessed high sensitivity, fast response and long-term stability. FDS hydrogel strain sensor can monitor various human motions in real time. Abstract: Polyvinyl alcohol (PVA) based hydrogels, are generally prepared by freeze–thaw cycling methods. However, water loss and shrinkage of the gel over time should be prevented during the freeze–thaw cycles. Herein, a polyvinyl alcohol-polyacrylic acid (PVA-PAA) double-network hydrogel was fabricated through the strategy of "freezing-drying-swelling" (FDS) cycle, where the moisture retention was unnecessary. By a freezing-drying treatment, the formation of PVA crystalline domains and hydrogen bonds in freezing step was further improved by the drying treatment, and subsequently enhanced the mechanical properties of the hydrogel. The FDS hydrogel with the cross-linker content of 0.1% and one FDS cycle (FDS-0.1-1) could reach the ultimate tensile stress as high as 1.1 MPa with high stretchability of 648% strain. Thanks to the combination of PAA and conductive ions, the FDS-0.1-1 hydrogel strain sensor possessed excellent conductivity with a wide strain monitoring range of 0–250%, high sensitivity with a gauge factor (GF) up to 3.985, a fast response (75 ms) and excellent long-term stability without any decay for 5000 cycles of continuous loading–unloading between 0 and 100% strain. Besides, the FDS hydrogel strain sensor can be used for real-time monitoring various movements of the human body, including large movements (finger, wrists, elbows, and back of the neck) and subtle motions (smile and swallow).